Pembelajaran berbasis proyek dan prestasi siswa dalam pendidikan kewarganegaraan: mengubah pendekatan pendidikan moral melalui pedagogi autentik - Luh Made Rismayati; I Made Yudana; Kadek Rihendra Dantes (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2025)
Citizenship and moral education face persistent global challenges, particularly in vocational secondary schools where students tend to prefer practical and contextualized learning experiences over abstract and teacher-centered instruction. Within this broader concern, the effectiveness of innovative pedagogical models in improving learning outcomes in citizenship education remains an important empirical question. This study examines the impact of Project-Based Learning (PjBL) on student achievement in Pancasila (citizenship) education. A quantitative approach employing a quasi-experimental pretest–posttest control group design was used. The participants consisted of two Grade X classes in an Indonesian vocational school: an experimental group receiving instruction through Project-Based Learning and a control group experiencing conventional teacher-centered instruction. Learning achievement data were collected using standardized achievement tests and analyzed through inferential statistical techniques to determine the significance of differences between groups. The findings indicate a statistically significant difference in posttest scores between students exposed to Project-Based Learning and those receiving conventional instruction, with the experimental group demonstrating higher learning achievement. These results provide empirical support for the instructional value of project-based pedagogies in citizenship education contexts, particularly within vocational settings that require more contextual and participatory approaches. This study contributes to the growing body of research on innovative pedagogy in moral and citizenship education by offering quasi-experimental evidence of Project-Based Learning’s effectiveness in enhancing academic achievement. The findings have broader implications for rethinking instructional strategies in citizenship education, especially in educational contexts seeking to bridge moral theory with authentic and practice-oriented learning experiences.